2022
DOI: 10.1136/jnnp-2022-329284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of cell-based assays in the characterisation of seronegative myasthenia gravis

Abstract: ObjectivePatients with myasthenia gravis without acetylcholine receptor (AChR) or muscle-specific kinase (MuSK) antibodies detected by radioimmunoprecipitation assays (RIAs) are classified as seronegative myasthenia gravis (SNMG). Live cell-based assays (l-CBAs) can detect additional antibodies to clustered AChR, MuSK and low-density lipoprotein receptor-related protein 4 (LRP4), but positivity rates are variable and both clinical relevance and utility of CBA platforms remain unclear.MethodsSera from 82 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 26 publications
(32 reference statements)
0
31
0
Order By: Relevance
“…It is important that all RIA-dSN but CBA-positive patients had typical MG clinical features and treatment response, with an overall milder disease severity and higher frequency of purely ocular forms, as already described in patients with clustered AChR MG or with MuSK Abs solely detected by CBA. 5 , 8 Notably, 2 patients, both with purely ocular MG, had Abs targeting only the fetal isoform of AChR, which highlights the importance of testing for these Abs to maximize the CBA sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important that all RIA-dSN but CBA-positive patients had typical MG clinical features and treatment response, with an overall milder disease severity and higher frequency of purely ocular forms, as already described in patients with clustered AChR MG or with MuSK Abs solely detected by CBA. 5 , 8 Notably, 2 patients, both with purely ocular MG, had Abs targeting only the fetal isoform of AChR, which highlights the importance of testing for these Abs to maximize the CBA sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, all sera were tested for Abs to the adult/fetal AChR and MuSK with an in-house live CBA and with the commercial fixed CBA (Euroimmun, Lubeck, Germany). 8 Samples were tested in the laboratories of the 2 institutions (n = 206 UCSC, Rome, Italy; n = 86 IRCCS Mondino Foundation, Pavia, Italy), using the same protocols briefly described as follows. Fixed CBA was performed according to the manufacturer's instructions (serum dilution 1:10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports showed that multiple sclerosis (MS) patients treated with anti-CD20 therapies were able to mount spike-specific T-cell responses comparable to patients not under B cell-depleting therapies. [ 13 , 14 ] To date, a single study reported the humoral and cell-mediated response (by an interferon gamma (IFN-γ) release assay in plasma) to mRNA vaccines in MG patients under different immunotherapies, including rituximab (RTX), [15] an anti-CD20 monoclonal antibody used as second-line treatment in MG. Here we employed a comprehensive immune profiling approach to determine the innate and adaptive immune response, including humoral and cellular response, to SARS-CoV-2 infection and mRNA vaccines in MG patients receiving RTX.…”
Section: Introductionmentioning
confidence: 99%